The maternal is political : women writers at the intersection of motherhood and social change - Strong, Shari MacDonald (Seal Press, 2008)
Exploring the vital connection between motherhood and social change, The Maternal Is Political features more than 40 powerful, hard-hitting literary essays by women who are striving to make the world a better place for children and families -- both their own and other women's -- in this country and globally. From the mom deconstructing playground "power games" with her first-grade child, to the mother who speaks out against misogyny during an awkward road trip with her college-age daughter and friends, to the mother of sons worrying about the threat of a future military draft, The Mate